2015
DOI: 10.1177/0961203315571463
|View full text |Cite
|
Sign up to set email alerts
|

Association of PELI1 polymorphisms in systemic lupus erythematosus susceptibility in a Chinese population

Abstract: In the Chinese Han population, PELI1 SNPs may be associated with SLE susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Published study demonstrated that PELI1 polymorphisms is genetically associated with SLE susceptibility in Chinese population 37 , we then collected PBMCs from healthy donors (HD) and SLE patients to investigate the potential role of PELI1 in regulating B cell-mediated immune response and SLE pathogenesis. Under healthy conditions, there are very few antibody-producing plasma cells detected in HD PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Published study demonstrated that PELI1 polymorphisms is genetically associated with SLE susceptibility in Chinese population 37 , we then collected PBMCs from healthy donors (HD) and SLE patients to investigate the potential role of PELI1 in regulating B cell-mediated immune response and SLE pathogenesis. Under healthy conditions, there are very few antibody-producing plasma cells detected in HD PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of Pellino1 and Pellino2 have been recorded in asthmatics , children with protracted bacterial bronchitis , and in transplant patients with acute kidney rejection . Furthermore, polymorphisms in the PELI1 locus, that encodes Pellino1, associate with vasculitis in young children and with increased susceptibility to systemic lupus erythematosus in a Chinese population . While the latter studies are restricted to interpreting association of Pellino genes and proteins with disease, a number of disease models have recently highlighted that Pellino proteins may play key roles in various pathogenic processes.…”
Section: Pellino Proteins As Regulators and Mediators Of Diseasementioning
confidence: 99%
“…The rs2607420 was related to risk of congenital megacolon in a Korean population (Kim et al ., 2017). In addition, rs329497 in PELI1 had a strong relationship with an autoimmune disease in a Chinese population (Chen et al ., 2015). In the present study, we genotyped these SNPs in a case-control cohort and evaluated their associations with CRC risk.…”
Section: Introductionmentioning
confidence: 99%